T1 mapping combined with arterial spin labeling MRI to identify renal injury in patients with liver cirrhosis - Xie, Shuangshuang; Chen, Mengyao; Chen, Chiyi; Zhao, Yumeng; Qin, Jiaming; Qiu, Caixin; Zhu, Jinxia; Nickel, Marcel Dominik; Kuehn, Bernd; Shen, Wen (Frontiers in Endocrinology, 2024)
Pur pose We investigated the capability and imaging criteria of T1 mapping and arterial spin labeling (ASL) MRI to identify renal injury in patients with liver cirrhosis.We recruited 27 patients with cirrhosis and normal renal function (cirrhosis-NR), 10 with cirrhosis and renal dysfunction (cirrhosis-RD) and 23 normal controls (NCs). All participants were examined via renal T1 mapping and ASL imaging. Renal blood flow (RBF) derived from ASL was measured from the renal cortex, and T1 values were measured from the renal parenchyma (cortex and medulla). MRI parameters were compared between groups. Diagnostic performances for detecting renal impairment were statistically analyzed. Results Cortical T1 (cT1) and medullary T1 (mT1) were significantly lower in the NCs than in the cirrhosis-NR group. The cortical RBF showed no significant changes between the NCs and cirrhosis-NR group but was markedly decreased in the cirrhosis-RD group. The areas under the curve (AUCs) for discriminating cirrhosis-NR from NCs were 0.883 and 0.826 by cT1 and mT1, respectively. Cortical RBF identified cirrhosis-RD with AUC of 0.978, and correlated with serum creatinine (r = -0.334) and the estimated glomerular filtration rate (r = 0.483). A classification and regression tree based on cortical RBF and cT1 achieved 85% accuracy in detecting renal impairment in the cirrhosis.Renal T1 values might be sensitive predictors of early renal impairment in patients with cirrhosis-NR. RBF enabled quantifying renal perfusion impairment in patients with cirrhosis-RD. The diagnostic algorithm based on cortical RBF and T1 values allowed detecting renal injury during cirrhosis.